MO758: Warfarin Treatment Quality and Outcomes in Patients with Non-Valvular Atrial Fibrillation and Chronic Kidney Disease Including Patients on Dialysis. (3rd May 2022) - Welander, Frida; Renlund, Henrik; Dimény, Emöke; Holmberg, Henrik; Själander, Anders
Abstract: BACKGROUND AND AIMS: Warfarin has traditionally been the drug of choice for patients with atrial fibrillation and GFR < 30 mL/min. Observational studies have shown a lower risk of ischemic stroke with warfarin compared with no treatment, but also an increased risk of bleeding [1 ]. For patients on dialysis, the role of warfarin is less clear due to high bleeding risk and diverging data on stroke protection [2, 3 ]. Warfarin treatment quality can be calculated as time in therapeutic range (TTR). TTR ≥ 70% is considered lowering the risk of adverse events [4 ]. The impact of a patient's individual TTR (iTTR) on ischemic stroke and bleeding is poorly investigated for patients with eGFR < 60 mL/min/1.73 m 2 including patients on dialysis, and the aim is to study this further. METHOD: A Swedish retrospective national cohort study investigating the risk of ischemic stroke and major bleeding in patients with non-valvular atrial fibrillation (NVAF) during warfarin treatment depending on iTTR (individual time in therapeutic range). Patients included have warfarin treated NVAF, eGFR < 60 mL/min or on dialysis, kidney transplant recipients excluded, between 2009 and 2018. Data extracted from Swedish high quality national health-care registries including Swedish Renal Registry for GFR-category, The Stroke Register for stroke-related outcomes and Auricula—the Swedish national quality register for AF and anticoagulation for warfarin treatment periods and INR measurements. ITTR is calculated in a 90-day Window and updated at each new INR value. The impact of iTTR is tested with the Cox regression and time-dependent covariates regarding risk for ischemic stroke, major bleeding (intracranial, gastrointestinal and other) and all-cause mortality. RESULTS: At enrolment of 2421 patients (29.1% female) 22.1% had G3 (eGFR 59–30 mL/min/1.73 m 2) 47.4% G4 (eGFR 15–29), 10.9% G5 (eGFR < 15) and 19.7% G5D (on dialysis). Mean iTTR for all patients was 64% (G3 71%, G4 66%, G5 61% and G5D 55%). The number of events, time on warfarin and event rates are found in Table 1 . Adjusted analysis shows that a 0.2 unit increase of iTTR lowers the risk of major bleeding for all patients, patients in G3–G5 and patients on dialysis (G5D) {hazard ratio 0.69 [95% confidence interval (95% CI) 0.61–0.78], 0.65 (0.55–0.77) and 0.78 (0.62–1.0)} (Fig. 1 ). Increased iTTR by 0.2 units does not seem to have a significant effect on the hazard of ischemic stroke for all patients, G3–G5 and G5D [HR 0.72 (95% CI 0.51–1.00), 0.77 (0.49–1.19) and 0.70 (0.36–1.37)]. An ITTR increase of 0.2 units lowers the risk of all-cause mortality for all patients, G3–G5 and G5D [0.62 (0.55–0.69), 0.56 (0.48–0.65) and 0.75 (0.62–0.9)]. ITTR > 70% compared with <70% lowers the risk of major bleeding and all-cause mortality in all patients [HR 0.63 (0.52, 0.76) and HR 0.52 (0.44, 0.61) but no significant effect on ischemic stroke (HR 0.61 (0.37, 1.01)]. CONCLUSION: Warfarin treatment quality worsens with decreasing GFR. Higher iTTR confers a lower risk of major bleeding and death for patients with NVAF and CKD, eGFR < 60 including dialysis. Conclusions cannot be made regarding the effect of iTTR and ischemic stroke due to few events. Patients with NVAF and chronic kidney disease including patients on dialysis on warfarin should be closely monitored to lower the bleeding risk.